2016
DOI: 10.1038/nrgastro.2016.17
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic pancreatic surgery for benign and malignant disease

Abstract: Laparoscopic surgery for benign and malignant pancreatic lesions has slowly been gaining acceptance over the past decade and is being introduced in many centres. Some studies suggest that this approach is equivalent to or better than open surgery, but randomized data are needed to assess outcomes. In this Review, we aim to provide a comprehensive overview of the state of the art in laparoscopic pancreatic surgery by aggregating high-quality published evidence. Various aspects, including the benefits, limitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
95
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(100 citation statements)
references
References 119 publications
3
95
0
2
Order By: Relevance
“…This shows that laparoscopy is safe regarding short-term outcomes which is in line with the current evidence of the literature [10]. Similarly, a review on laparoscopic surgery published in 2016 concluded that laparoscopic DP can be safely performed in high-volume centers, but that randomized controlled trials still have to confirm the effectiveness of the procedure [23]. A large propensity score-matching comparative study from Japan even showed that morbidity was diminished with laparoscopic DP along with intraoperative transfusion, and LoS [24].…”
Section: Discussionsupporting
confidence: 81%
“…This shows that laparoscopy is safe regarding short-term outcomes which is in line with the current evidence of the literature [10]. Similarly, a review on laparoscopic surgery published in 2016 concluded that laparoscopic DP can be safely performed in high-volume centers, but that randomized controlled trials still have to confirm the effectiveness of the procedure [23]. A large propensity score-matching comparative study from Japan even showed that morbidity was diminished with laparoscopic DP along with intraoperative transfusion, and LoS [24].…”
Section: Discussionsupporting
confidence: 81%
“…These suggestions were confirmed by several systematic reviews of cohort studies that reported reductions in intraoperative blood loss, blood transfusion, complications, wound infections and shorter hospital stay, and an increased rate of spleen preservation, all in favor of the minimally invasive approach [10, 11]. …”
Section: Introductionmentioning
confidence: 87%
“…Minimally invasive distal pancreatectomy (MIDP) was first described in 1994 by Cuschieri et al [9] Since then, several observational cohort studies from expert centers have suggested that MIDP is safe, feasible and cost-effective in the treatment of benign, premalignant and malignant lesions of the distal pancreas [10, 11]. These suggestions were confirmed by several systematic reviews of cohort studies that reported reductions in intraoperative blood loss, blood transfusion, complications, wound infections and shorter hospital stay, and an increased rate of spleen preservation, all in favor of the minimally invasive approach [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Spleen preserving laparoscopic distal pancreatectomy is considered as first choice operation for patients with benign or small low-grade malignant tumors of the body or tail of the pancreas, such as cystic tumors, IPMN, or even chronic pancreatitis (8). For pancreatic adenocarcinoma, laparoscopic en bloc resection of pancreatic tail, lymphadenectomy with splenectomy is the procedure of choice, demonstrating better oncological outcomes (5-year overall survival was 33%)(9,10).…”
Section: Discussionmentioning
confidence: 99%